Estudio sobre las funciones de los comités de padres de familia que señala la ley orgánica de educación intercultural y su aplicabilidad en todas las directivas de educación general básica de la unidad educativa municipal Pradera, de la ciudadela La Pradera, parroquia San Sebastián, cantón y provincia de Loja, año lectivo 2012–2013 - Roblez Vargas, Margarita de Jesús (2014)
The developed research is characterized by a study in the implementation of the functions of the family parents committees that designates the law of Intercultural education and its applicability in all directives of General basic education of the Municipal Prairie educational unit of the ciudadela La Pradera, San Sebastian parish, canton and Loja province, school year2012-2013, the purpose is to understand and determine the level of knowledge that parents have about the functions to be fulfilled with respect to the charge that represent.The school has 210 students enrolled. For research was taken as shown in 32 parents that form committees of parents of family of 8 grades, 8 teachers and 4 Presidents of the second level students. To test the hypothesis was used, the scientific method to discover the internal relations of the subject, its causes and effects; the deductive method, determined the specific problems being investigated; the hypothetical method allowing to raise the unifying hypothesis as axes of research; and with the deductive conclusions. The general objective is to: analyze the role of family committees of parents within the Prairie Municipal educational unit. For the achievement of the objective research instruments corresponding to the technique of the survey were designed, these instruments constitute questionnaires applied to key informants as: Director, teachers, students and parents of the institution.It is concluded, that members who join committees unknown nfunctions that they must perform as committees of parents, this fact does not prevent that committees take effect multiple activities for the benefit of the needs required by the educational institution, since they have contributors parents, looking for ways to not engage teachers in decision-making and prevent infliction of educational laws. Therefore, it is recommended that teachers made known at the beginning of the new school year functions that the parents must meet regarding what designates the law of Intercultural education.